2021
DOI: 10.1186/s12913-021-06994-0
|View full text |Cite
|
Sign up to set email alerts
|

Number of musculoskeletal pain sites leads to increased long-term healthcare contacts and healthcare related costs – a Danish population-based cohort study

Abstract: Background People with musculoskeletal pain seek more healthcare than the general population, however little is known about the long-term effect on healthcare use. The aim of this study was to examine the consequences of number of musculoskeletal pain sites on long-term care-seeking and healthcare-related costs and explore how health anxiety influences this relationship. Methods We conducted a Danish population-based longitudinal cohort study of 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Pain sites served as a covariate for global pain severity in the model since the other pain measures were limited to the knee 45 . Increasing number of pain sites has been linked to worse health outcomes and three or more pain sites are considered widespread pain 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Pain sites served as a covariate for global pain severity in the model since the other pain measures were limited to the knee 45 . Increasing number of pain sites has been linked to worse health outcomes and three or more pain sites are considered widespread pain 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%
“…15 Identifying LBP phenotypes is relevant because co-occurring MSK pain is associated with more negative consequences, such as reduced workability, increased healthcare utilization, and poorer response to treatment compared with single-site MSK pain. 2,6,19,20,26,29,43,48 However, counting the number of pain sites may be too simplistic because certain pain sites or pain patterns among people with persistent LBP may have diverse consequences and affect prognosis or treatment outcomes differently. 27 Distinct LBP phenotypes may have features requiring a stratified care approach, 53 and including them in the management of LBP rather than approaching LBP as a single entity could offer the possibility of larger treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…15 Identifying LBP phenotypes is relevant because co-occurring MSK pain is associated with more negative consequences, such as reduced workability, increased healthcare utilization, and poorer response to treatment compared with single-site MSK pain. 2,6,19,20,26,29,43,48 However, counting the number of pain sites may be too simplistic because certain pain sites or pain patterns among people with persistent LBP may have diverse Sponsorships or competing interests that may be relevant to content are disclosed at the end of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pain frequently affects multiple anatomical sites in the same individual (Carnes et al, 2007; Hartvigsen, Davidsen, et al, 2013; Hartvigsen, Natvig, & Ferreira, 2013), impacting importantly on daily functioning (Kamaleri et al, 2008a; Saastamoinen et al, 2006), work ability, healthcare seeking (Mose et al, 2021) and sickness absence (Neupane et al, 2015). We have previously shown large international differences in the prevalence of multi‐site pain among working populations (Coggon et al, 2013), while other research has suggested that within individuals, the extent of musculoskeletal pain (as indicated by the number of anatomical sites affected) remains fairly constant over periods of 2 years or longer (Christensen et al, 2017; Kamaleri et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%